2015
DOI: 10.1016/j.jmgm.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a carboxylic esterase RhEst1 based on computational analysis of substrate binding

Abstract: A new carboxylic esterase RhEst1 which catalyzes the hydrolysis of (S)-(+)-2,2-dimethylcyclopropanecarboxylate (S-DmCpCe), the key chiral building block of cilastatin, was identified and subsequently crystallized in our previous work. Mutant RhEst1A147I/V148F/G254A was found to show a 5-fold increase in the catalytic activity. In this work, molecular dynamic simulations were performed to elucidate the molecular determinant of the enzyme activity. Our simulations show that the substrate binds much more strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Detailed analysis of the distance between the carbonyl group of the substrate and the catalytic Ser134 is shown in Figure S1, and the result demonstrates that the substrate binding position is distant from the catalytic residues. Furthermore, we found a strong π–π stacking interaction between the benzene ring of the Phe92 residue and the benzene ring of the catalytic Tyr175 residue, which forms a spatial barrier that blocks substrate binding with the catalytic residues, as has been observed previously for esterases . We speculated that F92 is a key residue affecting the activity of Cg KR1; hence, it was chosen for mutagenesis.…”
Section: Results and Discussionsupporting
confidence: 59%
“…Detailed analysis of the distance between the carbonyl group of the substrate and the catalytic Ser134 is shown in Figure S1, and the result demonstrates that the substrate binding position is distant from the catalytic residues. Furthermore, we found a strong π–π stacking interaction between the benzene ring of the Phe92 residue and the benzene ring of the catalytic Tyr175 residue, which forms a spatial barrier that blocks substrate binding with the catalytic residues, as has been observed previously for esterases . We speculated that F92 is a key residue affecting the activity of Cg KR1; hence, it was chosen for mutagenesis.…”
Section: Results and Discussionsupporting
confidence: 59%
“…4b ). During hypoxia, mitochondria increased generation of reactive oxygen species (ROS) [ 25 ], which activated mitogen-activated protein kinase (MAPK) [ 26 ]. Hypoxic conditions also lead to cell cycle arrest [ 27 , 28 ] and apoptosis by a number of HIF-1-mediated and independent pathways [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The melting temperature ( T m ) of Rh Est1 M2 was 1.7 °C higher than that of its parent Rh Est1 M1 and nearly 11 °C higher than that of the wild type (Table ). All-atom MD simulations indicated that α-helices and loops in the cap domain exhibit high fluctuations, showing relatively high B-factors . Mutations of these sites might greatly improve the enzyme thermostability and simultaneously decrease the thermal motion and positional disorder of these sites .…”
Section: Resultsmentioning
confidence: 99%
“…All-atom MD simulations indicated that α-helices and loops in the cap domain exhibit high fluctuations, showing relatively high Bfactors. 21 Mutations of these sites might greatly improve the enzyme thermostability and simultaneously decrease the thermal motion and positional disorder of these sites. 22 The improvement of thermostability for this enzyme has provided a significant clue that indicates the relationship between cap domain engineering and enzyme thermostability.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%